Politics of inclusion : castes minorities and affirmative action - "Hasan, Zoya" (New Delhi, 2009)
Post-Mandal, the demand for reservations by various groups has become a consistent feature of Indian politics. Yet, the focus remains on caste, with little attention paid to the under-representation of religious minorities in India. The book takes up the case of relative disadvantage and interogates the multiple and overlapping dimensions of deprivation. Hasan argues that, in view of the comparative evidence avaiable, presently excluded and disadvantaged groups should also qualify for affirmative action. This book will interest students and scholars of Indian politics, sociology, and history.
Keywords: Politics-Minorities